2015
DOI: 10.1088/0004-637x/809/2/109
|View full text |Cite
|
Sign up to set email alerts
|

Broad Balmer Wings in Ba Hyper/Supergiants Distorted by Diffuse Interstellar Bands: Five Examples in the 30 Doradus Region From the VLT-Flames Tarantula Survey

Abstract: Extremely broad emission wings at Hβ and Hα have been found in VFTS data for five very luminous BA supergiants in or near 30 Doradus in the Large Magellanic Cloud. The profiles of both lines are extremely asymmetrical, which we have found to be caused by very broad diffuse interstellar bands (DIBs) in the longward wing of Hβ and the shortward wing of Hα. These DIBs are well known to interstellar but not to many stellar specialists, so that the asymmetries may be mistaken for intrinsic features. The broad emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…The GOSSS spectral classification is very similar, O7Ib(f). CygOB2-A11 is 1 8 away from CygOB2-12, a well known, highly extinguished B hyper/ supergiant (Morgan et al 1954;Walborn et al 2015) which we placed on the slit and for which we found a spectral type of B5Ia. Note, however, that this star is a photometric variable (Salas et al 2015) and that for late B stars the He Iλ4471/Mg IIλ4481 ratio is luminosity dependent, which leads to differing spectral subtypes in the literature (Clark et al 2012).…”
Section: New Systems In Gosssmentioning
confidence: 71%
“…The GOSSS spectral classification is very similar, O7Ib(f). CygOB2-A11 is 1 8 away from CygOB2-12, a well known, highly extinguished B hyper/ supergiant (Morgan et al 1954;Walborn et al 2015) which we placed on the slit and for which we found a spectral type of B5Ia. Note, however, that this star is a photometric variable (Salas et al 2015) and that for late B stars the He Iλ4471/Mg IIλ4481 ratio is luminosity dependent, which leads to differing spectral subtypes in the literature (Clark et al 2012).…”
Section: New Systems In Gosssmentioning
confidence: 71%
“…The systematic decline of the narrow emission at Hγ among the three epochs is noteworthy. Hβ shows the the broad wings discussed by Walborn et al (2015) with an asymmetry ascribed to a diffuse interstellar band in the longward wing; unusually, strong and broad Balmer emission extends down to Hδ, as in the Galactic LBV HRCarinae (Hutsemékers & Van Drom 1991). In contrast, the 2016 spectrum has metamorphosed into an AF type dominated by a plethora of strong Fe II absorption lines, although the broad Balmer emission remains.…”
Section: Hde 269216mentioning
confidence: 85%
“…It shows an impressive systematic evolution from predominantly emission line before the outburst, through a PCyg profile with multiple/ variable absorption components in 2009 during the late rise in light, to a symmetrical albeit variable "Be" absorption with emission wings, or alternatively a broad, centrally reversed emission at maximum. However, as discussed and referenced by Walborn et al (2015), such a profile does not necessarily correspond to a disk, as it can be produced by radiativetransfer effects in a spherical envelope. As usual, this line will provide vital diagnostics of the unknown LBV outer structure as a function of time, even within the visual light maximum.…”
Section: R71mentioning
confidence: 99%
See 1 more Smart Citation
“…6) shows an asymmetric nebula around it with a direction consistent with the corrected proper motion. The nebula does not have the typical shape of a bow shock but that could be due to the extremely high mass-loss rate of this object (Lennon et al 1992;Walborn et al 2015), which could produce a more filled structure. HD 190 603 is moving westwards close to the Galactic Plane and its likely origin is in one of the Cygnus OB associations.…”
Section: Ba Supergiantsmentioning
confidence: 99%